Gray tensors on lightlike hypersurfaces - ATINDOGBE, COMLAN CYRIAQUE; BERARD BERGERY, Lionel; TOSSA, JOEL (My University, 2009)
This paper introduces Gray-tensors on lightlike hypersurfaces M n+1 of signature (0, n), (n ≥ 1) and investigates on their basic properties in connec- tion with their null geometry. In particular, we show that there is an interplay between existence of Gray-tensors of certain type and lightlike warped product structures. As a physical relevance, we show that there exists such a tensor on both globally Killing horizons (GKH) and totally geodesic lightlike triple warped product hypersurfaces.
Keywords: Lightlike hypersurface; screen distribution; Gray-tensor; almost product; structure; warped product.